A Critical Review of Yang and Plakansâ Strategy Inventory for Integrated Writing - Karimullah, Imam Wahyudi (JU-ke: Jurnal Ketahanan Pangan, 2018)
This article reviews Yang and Plakansâ (2012) Strategy Inventory for Integrated Writing (SIIW). The existence of SIIW is crucial to elicit strategies used by TOEFL iBT test takers in completing integrated reading-listening-writing task. After reviewing Yang and Plakansâ SIIW, it is found that there is a need to develop a more comprehensive, reliable and valid strategy inventory for integrated writing.Â Keywords: strategy inventory, integrated writing